Impact of gender on the negotiating performance:Case Administrative Sciences Faculty - Bocca Ruiz, Fernando F.; Olivero Arias, Edison; Alvarado Márquez, Mariana (Revista Universidad de Guayaquil, 2016)
A qualitative study on gender behavior when negotiating male and female students of the Faculty of Administrative Sciences at the University of Guayaquil is presented. It seeks to determine if male students get results that differ from those obtained by female students in negotiation exercises done in class. It begins by describing the general stereotypical characteristics of negotiators, for men and women and how these affect the negotiation process. Then, special traits found in the class of Trade Negotiations about the proposed cases are explored. Data collected during the study of cases allow a statistical correlationbetween genders and trading performance in addition to prove the validity of assumptions of stereotypes for men and women during the negotiations. Finally, the implications of findings are analyzed and conclusions on the outcome of negotiations among male and female students are extracted.
Keywords: gender difference; negotiation; behavior; University of Guayaquil; men